Gender and torture. Simone de Beauvoir and Gisèle Halimi regarding the case of Djamila Boupacha - Bea Pérez, Emilia (DERECHOS Y LIBERTADES: Revista de Filosofía del Derecho y derechos humanos, 2021)
The first complaint about sexual violence as a form of torture in the Algerian war concerns Djamila Boupacha. Her case was defended in the Algerian and French courts by the feminist lawyer Gisèle Halimi, and it had a massive public impact thanks to the support of Simone de Beauvoir and the mobilisation of a committee composed mainly of women, which sought to raise the political and legal profile of a matter which was destined to remain hidden. The paper assesses the anti-colonial and anti-patriarchal stance on which it is based, analyses the entire judicial process, and highlights the issues that herald the evolution of law towards gender justice.